The synthesis and reactivity of functionalised alkyl transition metal complexes - Friedrich, Holger Bernhard (University of Cape Town, 2016)
Includes bibliographical references. === The complexes [CpFe(CO)₂CH₂X] and [CpW(CO)₃CH₂X] (Cp = n⁵-C₅H₅; X=Cl, Br, I) have been prepared and their reactivity with a series of tertiary phosphines, amines, SMe₂ and AsPh₃ in THF, CH₃CN and MeOH has been investigated. Two types of cationic products, namely the ylide complexes [CpM(CO)nCH₂L]+ or the disubstituted complexes [CpML₂(CO)n-l]+ (M = Fe, n = 2; M = W, n = 3) were obtained, depending on the halide (X), the ligand (L), the metal (M) and the solvent used. The variables X, L, M and the solvent used were also all found to influence the rates of the reactions. Thus the relative reaction rates of the complexes [CpFe(CO)₂CH₂Br] and [CpW(CO)₃CH₂Br] with L were determined by 1 H NMR spectroscopy and found to increase with increasing pKa and decreasing cone angle of L. In general, the rate of reaction of [CpFe(CO)₂CH₂X] and [CpW(CO)₃CH₂X] with L increases in the sequence Cl < Br < l and the reactions of [CpFe(CO)₂CH₂X] with L are significantly faster than the corresponding reactions of [CpW(CO)₃CH₂X]. The reactions of [CpFe(CO)₂CH₂Br] and [CpW(CO)₃CH₂Br] with dppe {dppe = bis(diphenylphosphino)ethane} yield the bridged dicationic ylide complexes [{Cp(CO)₂FeCH₂}₂{PPh₂(CH₂)₂PPh₂}] and [{Cp(CO)₃WCH₂}₂{PPh₂(CH₂)₂PPh₂}] respectively.